1998
DOI: 10.1016/s0885-3924(97)00260-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Ambulatory AIDS Patients

Abstract: Although preliminary reports indicate that fatigue is a common symptom of human immunodeficiency virus (HIV) disease, little empirical research has focused on its prevalence or characteristics among patients with acquired immunodeficiency syndrome (AIDS). We assessed the frequency of fatigue and its medical and psychological correlates, in a cross-sectional survey of ambulatory AIDS patients. Ambulatory patients with AIDS who participated in a study of quality life (N = 427) were classified into fatigue/no fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 14 publications
10
130
2
Order By: Relevance
“…Other studies have also reported it to be one of the common problems. [22,[28][29][30] Fatigue has a multifactorial origin [22,29,31] that includes lack of rest or exercise, improper or inadequate diet, psychological stress, anemia, infection, thyroid abnormalities, side effects of medication, sleep disturbances, and fever. Fatigue has not been found to correlate with CD4 counts, [31,32] and this was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also reported it to be one of the common problems. [22,[28][29][30] Fatigue has a multifactorial origin [22,29,31] that includes lack of rest or exercise, improper or inadequate diet, psychological stress, anemia, infection, thyroid abnormalities, side effects of medication, sleep disturbances, and fever. Fatigue has not been found to correlate with CD4 counts, [31,32] and this was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent problems of our study -fatigue and emotional problems -often coexist and are interrelated. [29] Many physiological markers and psychological constructs are available for objective assessment of fatigue. [31,33] There is a need for routine assessment and management of fatigue in patients with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia may occur as a result of HIV-induced ineffective hematopoiesis, opportunistic infections, infiltrative disease of the bone marrow, nutritional deficiencies, hemolysis, or antiretroviral or other therapy (Breitbart et al, 1998;Ferri et al, 2001;Groopman, 1998;Mocroft et al, 1999;Moore, 1999 (Bartlett & Gallant, 2000;Koch et al, 2001), and as noted above, cytokine release could influence hepatic dysfunction. There is a high prevalence of hepatitis C in seropositive people: it is estimated that 300,000 of the 750,000 HIV-infected individuals in the United States are coinfected with the hepatitis C virus (HCV).…”
Section: Hiv-related Fatigue; Physiological Variables; Biomarkersmentioning
confidence: 99%
“…Some researchers speculate that HIV-related fatigue is a result of physiological factors, whereas others argue that it is a function of psychosocial variables. This report focuses on the relationship of physiological variables and HIV-related fatigue.Address all correspondence to Julie Barroso, Duke University School of Nursing, DUMC 3322, Durham, NC 27710, phone: (919) Barroso, Carlson, & Meynell, 2003;Breitbart, McDonald, Rosenfeld, Monkman, & Passik, 1998;Justice et al, 1999;Perkins et al, 1995; Sullivan, Dworkin, & the Adult and Adolescnt Spectrum of HIV Investigators, 2003;Vlahov et al, 1994;Vogl et al, 1999; Voss, 2002). Henderson, Safa, Easterbrook, & Hotopf (2005) actually found greater fatigue in individuals with higher CD4 counts.…”
mentioning
confidence: 99%
“…Many of the people living with HIV/AIDS find it challenging to attend to the daily routine tasks of living or participate in moderate to vigorous physical activities, or have sufficient energy or vitality to engage in an active social life while managing HIV/AIDS. Fatigue or low energy has been associated with both physical and psychological morbidity and poor quality of life in persons with HIV/AIDS [18,19]. In addition; fatigue and a CD4 T cell count less than 500 are associated with physical limitations and disability [20].…”
Section: Introductionmentioning
confidence: 99%